Intra-Hepatic Spillage of Gallstones as a Late Complication of Laparoscopic Cholecystectomy: MR Imaging Findings - Ragozzino, Alfonso (Pol J Radiol, 2016)
BACKGROUND: Spillage of gallstones in the abdominal cavity may rarely occur during the course of laparoscopic cholecystectomy. Dropped gallstones in the peritoneal and extra-peritoneal cavity are usually asymptomatic. However, they may lead to abscess formation with an estimated incidence of about 0.3%. Common locations of the abscess are in the abdominal wall followed by the intra-abdominal cavity, usually in the sub-hepatic or retro-peritoneum inferior to the sub-hepatic space. CASE REPORT: We hereby describe an unusual case of infected spilled gallstones in the right sub-phrenic space, prospectively detected on abdominal MRI performed two years after laparoscopic cholecystectomy, in a patient with only a mild right-sided abdominal complaint. CONCLUSIONS: This case highlights the role of MRI in suggesting the right diagnosis in cases with vague or even absent symptomatology. In our case the patient’s history together with high quality abdomen MRI allowed the correct diagnosis. Radiologists should be aware of this rare and late onset complication, even after many years from surgery as an incidental finding in almost asymptomatic patients.